The Impact of Digital Governance on Public Service Efficiency: A Cross-Country Analysis - Sadat, Anwar; Lawelai, Herman; Yudarsat, Andre Putra (Jurnal Pemerintahan dan Politik Lokal, 2025)
The increasing adoption of digital governance has significantly transformed public service delivery, aiming to improve efficiency, transparency, and citizen involvement. This study explores the impact of digital governance on public service efficiency, focusing on a cross-country comparison between industrialized and developing nations. The primary goal is to understand how digital governance influences service delivery in various contexts and to identify factors that contribute to its success. Using a mixed-methods approach, the study combines quantitative analysis of digital governance adoption and public service efficiency with qualitative insights from interviews with government officials and experts. The results show that digital governance enhances efficiency in countries with advanced digital infrastructure and institutional support, reducing processing times, costs, and improving citizen satisfaction. However, in developing countries, benefits were limited due to challenges such as poor infrastructure, lack of training, and political instability. The study emphasizes the importance of infrastructure, political will, legal frameworks, and digital literacy in determining the effectiveness of digital governance. The novelty of this research lies in its cross-country approach, offering new insights into optimizing digital governance strategies across different national contexts. Recommendations for policymakers include enhancing infrastructure, fostering political commitment, and improving digital literacy to maximize the potential of digital governance for better public service delivery.